A hydroxamic-acid-containing nucleoside inhibits DNA repair nuclease SNM1A - Mcgouran, Joanna; Senge, Mathias; Scanlan, Eoin (My University, 2019)
Nine modified nucleosides, incorporating zinc-binding pharmacophores, have been synthesised and evaluated as inhibitors of the DNA repair nuclease SNM1A. The series included oxyamides, hydroxamic acids, hydroxamates, a hydrazide, a squarate ester and a squaramide. A hydroxamic acid-derived nucleoside inhibited the enzyme, offering a novel approach for potential therapeutic development through the use of rationally designed nucleoside derived inhibitors.
PUBLISHED
Keywords: DNA repair; Nuclease SNM1A; Cancer treatment